MENINGKATKAN KEMAMPUAN MENGENAL HURUF A-Z MELALUI MEDIACCANTOL KARTUHHURUFPPADAAANAK KELOMPOKaAdDI RA JA’FARIYAH DESA KANTEN KECAMATAN TRUCUK KABUPATEN BOJONEGORO TAHUN PELAJARAN 2019/2020. - Priheni, Siti; Apriliyana, Firdausi Nuzula (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2024)
In learning the ability to recognize letters a-z in group A in RA Ja'Fariyah Kanten Village, Trucuk sub-district, Bojonegoro Regency, there are still many students who have not been able to show letter symbols, recognize initial letters and mention letter symbols according to sound. Therefore an effort is needed to improve the child's ability to recognize the letter a-z, namely through the medium of cantol letter cards. This study aims to determine the increase in children's ability to recognize the letter a-z in group A children in RA Ja'Fariyah, Kanten Village, Trucuk District Bojonegoro Regency 2019/2020 school year through letter card cantol media. This research is a Classroom Action Research (CAR) which was conducted in two cycles. Each cycle has 4 stages, namely research planning, action implementation, observation (observation) and reflection. The subjects in this study were the children of group A RA Ja'Fariyah, Kanten Village, Trucuk District, Bojonegoro Regency with a total of 15 children and an early childhood education teacher. The data in this study are observation and documentation. The data collected are student learning outcomes and teacher observations. This study is said to be successful or complete individual learning outcomes ≥ 65% and a class is said to be complete learning if there is ≥85%. Class completeness cycle reaches 40% after action is taken in cycle I class completeness reaches 60% and in cycle II children's learning completeness reaches 87%. The research results show that in cycle I class learning completeness has not been achieved, while in cycle II children's learning completeness has been achieved